1997
DOI: 10.1071/wr96033
|View full text |Cite
|
Sign up to set email alerts
|

Population Ecology and Reproductive Seasonality in Three Species of Antechinus (Marsupialia : Dasyuridae) in the Wet Tropics of Queensland

Abstract: The population and reproductive ecologies of three sympatric species of antechinus were examined in upland rainforests in the wet tropics of Queensland. The three species, Antechinus stuartii adustus, A. flavipes rubeculus and A. godmani, exhibited unusually low trapping success compared with that of sites in temperate regions of Australia. Spatial distributions were extremely patchy both between and within study sites. Comparison with trapping data for temperate populations of A. stuartii and A. flavipes sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…2) ovulates between mid‐June and mid‐July (i.e. just around the winter solstice, Van Dyck, 1982a; Watt, 1997), up to 3 months before the populations of A. flavipes flavipes in southern Queensland which ovulate between early August and mid−late September. Antechinus flavipes rubeculus mates at a rate of change of photoperiod of −25 to +25 s/day and at absolute photoperiods of between 11 h and 11 h 20 min.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2) ovulates between mid‐June and mid‐July (i.e. just around the winter solstice, Van Dyck, 1982a; Watt, 1997), up to 3 months before the populations of A. flavipes flavipes in southern Queensland which ovulate between early August and mid−late September. Antechinus flavipes rubeculus mates at a rate of change of photoperiod of −25 to +25 s/day and at absolute photoperiods of between 11 h and 11 h 20 min.…”
Section: Resultsmentioning
confidence: 99%
“…These three taxa can be found sympatrically within the rainforests of northern Queensland (Watt, 1997), and all mate around the winter solstice, where neither rate of change of photoperiod nor absolute photoperiod differ by much. Watt (1997) reported that there was little synchrony in the timing of births of A. flavipes rubeculus , although all males were dead by mid‐August, suggesting synchrony remaining in the male die‐off physiology. Because of scant data on the reproductive activity of all three species, it is difficult to know how clearly separated their reproductive efforts are.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our result that in insectivorous dasyurids, population density is lowest at low latitude supports Johnson's (1998a) finding that Australian forest mammals are rarest in the tropics. It also corroborates Watt's (1997) discovery that population densities of antechinus in the wet tropics are some of the lowest anywhere in their distribution. Our study suggests that antechinus populations, and likely other insectivorous dasyurids in forest habitats, are regulated by winter arthropod availability, which is driven by amount of winter rainfall (Figures 3.2, 3.3 and 3.4).…”
Section: Discussionsupporting
confidence: 84%
“…Antechinus have a short mating season (rut), which lasts for approximately one to three weeks during winter or early spring. The exact timing differs between species and sites (McAllan et al, 2006;Watt, 1997;Woolley, 1966). Evidence suggests that breeding timing is triggered by rate of change of photoperiod, and species in Queensland appear to have longer breeding seasons than species in southern Australia (McAllan et al, 2006).…”
Section: Dasyuridae and The Genus Antechinusmentioning
confidence: 99%